Strategi Pengembangan Kemampuan Membaca Permulaan di Ra Al-Kamal - Hairani Ananda Putri; Anggi Annisa Pohan; Nita Hayati; Rahmania Hasibuan; Nabila Dwirizki Handayani (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Early literacy materials can give a person softness of heart, critical thinking skills and creative understanding. The purpose of this study was to understand the ways in which teachers teach group B children aged 5-6 years about the concept of reading and to identify factors that may hinder the successful implementation of these strategies. This study utilized a qualitative method with a descriptive approach. Data was collected by conducting observations, interviews and documentation. The research noted that teachers apply a variety of strategies in introducing core reading concepts including; whiteboard media as an opener, coloring as a habituation in recognizing letters, letter guessing games with smart wall media, storytelling, stage books. The implementation of these strategies has been quite optimally done at Ra Al-Kamal because the teachers are very enthusiastic and fast so that the learning process is carried out conducively.